NURTURING CREATIVITY THROUGH ART APPRECIATION - Susmita Lakhyani (European Scientific Journal, ESJ, 2014)
Problem statement: Art Education has been given place in the curriculum yet there is ageneral misconception that the subject Art is of lesser importance and treated as a mere entertainingfringe. The present study looks into this matter. The basic key question, therefore, is-Does process of‗art appreciation‘, a significant component ofart education, promote creative aspects of students and facilitate in attaining the educational objectives. Itis with reference to Teacher education course. Approach: For the study, a workshop on art appreciation wasorganized and 200 B.Ed. students (pre-service teachers) were taken. Most of these students had studiedart only till 8th standard while few of them had no experience of any art class in school. They werehesitant to paint and had lot of misconceptions about art. The workshop included slide show on works of art,discussion and interpretation; viewing andcommuning with the work in silence with instrumental music in the background;writing theinterpretations/ reflections on the displayed paintings ofone‘s choice in the workshop; and feedback on overall experience. Data was analyzed qualitatively. Results: It was concluded that art appreciation promotes, unique, independent, and honest perception; inculcates courage and confidence to express; helps to explore inner self and make symbolic association; integrate ideas; develop feelings, non-verbal expression,joy, peace and appreciation of nature; and involves sharpening of senses.Therefore, art appreciation promotes creative aspects and facilitates in attaining educational objectives.